NEW APPROACHES IN MATHEMATICS EDUCATION: THE REGIONAL DEVELOPMENT CONCEPT OF MATHEMATICS EDUCATION - Yusupova, Olga; Ibyatova, Lyaysan (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This project focuses on development of Maths’ popularity among students. The aim of the research is to preserve and improve the traditions in Mathematics education in the Samara region. The article then extends different methods and strategies of gaining popularity in mathematical knowledge in the region. The methodology of the research was held of using secondary data, also the results of several projects, which were launched in this field, were used. As a result, this approach offers continued support and ultimately increases students’ achievements, engagement and retention. In addition, the authors made a comparison between the previous and future projects in order to show the gap in methodologies in Mathematics education.